Effect of water stress on renewable energy from sugarcane biomass (2019)
The higher heating value (HHV) of sugarcane biomass components has been well documented; however, the effect of different soil water levels (abiotic stress) during the growing season on HHV has not been assessed for this energy crop. Drip irrigation in sugarcane production presents a potential to be a disruptive technology for sugarcane mills in terms of water-energy-nexus, making this inextricable relationship more efficient. The objective of this article was to quantify the higher heating value and useful energy from biomass partitions of different sugarcane varieties (Saccharum spp.) drip irrigated at four water levels and four maturation processes (drying off intensity prior to harvesting time); this information is not available in literature to date. The contribution of this article to the state of the art of knowledge are: a) the heating values for sugarcane partitions: bagasse, leaves and pointers did not vary significantly for varieties, water stress levels under drip irrigation and maturation processes; conversely, the heating value for the sheath biomass partition vary significantly for varieties. The average heating values for all treatments for the bagasse, sheaths, leaves and pointers were 18.16, 17.21, 17.64 and 17.84 MJ kg−1 respectively; b) the useful energy in sugarcane is almost totally dependent on the biomass produced per unit of area; drip irrigation levels and sugarcane variety traits are important in establishing the bioenergy productivity per area; the average value obtained for all treatments was 660.29 GJ ha−1 year−1 (36.90 Mg dry mass ha−1 year−1). Drip irrigated sugarcane crops at higher water levels in the soil, resulted a higher intensive land use and less deforestation pressure at sugarcane bioenergy production areas.